Pengaruh Konsistensi Pengakuan Pendapatan (PSAK 72) dan Transparansi Laporan Keuangan Terhadap Nilai Perusahaan Syariah - Fitria RaudatulHusna; Youdhi Prayogo; Faturahman Faturahman (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
This study aims to analyze the effect of income recognition consistency (PSAK 72) and financial statement transparency on firm value in Islamic property and real estate companies listed on the Indonesia Sharia Stock Index (ISSI) during the 2020–2024 period. This research uses a quantitative approach with panel data regression analysis. The sample consists of 40 firm-year observations. The results show that income recognition consistency (PSAK 72) has no significant effect on firm value, with a significance value of 0.4815. Financial statement transparency also has no significant effect, with a significance value of 0.8545. Simultaneously, both variables do not significantly affect firm value, with a significance value of 0.776118. The Adjusted R-Square value of -0.039712 indicates that the independent variables have a very low ability to explain the dependent variable. The conclusion of this study is that firm value in the Islamic property and real estate sector is more influenced by other factors outside the research model, such as market conditions, profitability, and capital structure. These findings indicate that financial reporting quality does not always have a direct impact on firm value in certain industry contexts.